1997
DOI: 10.1083/jcb.136.6.1307
|View full text |Cite
|
Sign up to set email alerts
|

Actin Depolymerizing Factor (ADF/Cofilin) Enhances the Rate of Filament Turnover: Implication in Actin-based Motility

Abstract: Actin-binding proteins of the actin depolymerizing factor (ADF)/cofilin family are thought to control actin-based motile processes. ADF1 from Arabidopsis thaliana appears to be a good model that is functionally similar to other members of the family. The function of ADF in actin dynamics has been examined using a combination of physical–chemical methods and actin-based motility assays, under physiological ionic conditions and at pH 7.8. ADF binds the ADPbound forms of G- or F-actin with an affinity two orders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
1,010
8
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 956 publications
(1,115 citation statements)
references
References 64 publications
(121 reference statements)
80
1,010
8
7
Order By: Relevance
“…ADF/cofilin binds both to G-and F-actin and enhances actin dynamics by severing actin filaments and increasing their depolymerization from the pointed end (Carlier et al 1997;Gungabissoon et al 1998). Since the activity of ADF/cofilin on the actin cytoskeleton has been studied in detail, and since ADF9 provides a potential link from BBM signaling to actin dynamization, we chose to further characterize the up-regulation of ADF9 in 35S::BBM:GR seedlings.…”
Section: Bbm Dynamizes the Actin Cytoskeletonmentioning
confidence: 99%
“…ADF/cofilin binds both to G-and F-actin and enhances actin dynamics by severing actin filaments and increasing their depolymerization from the pointed end (Carlier et al 1997;Gungabissoon et al 1998). Since the activity of ADF/cofilin on the actin cytoskeleton has been studied in detail, and since ADF9 provides a potential link from BBM signaling to actin dynamization, we chose to further characterize the up-regulation of ADF9 in 35S::BBM:GR seedlings.…”
Section: Bbm Dynamizes the Actin Cytoskeletonmentioning
confidence: 99%
“…The ADF/cofilin family has emerged as a central regulator of actin turnover in eukaryotes including plants [Bamburg, 1999;Maciver and Hussey, 2002;Van Troys et al, 2008]. Through its AF severing and pointed enddepolymerizing activities, ADF/cofilin enhances actin cytoskeleton dynamics [Carlier et al, 1997;Blanchoin and Pollard, 1999;Pavlov et al, 2007]. Dong et al [2001] reported that both an increase and a decrease of the Arabidopsis ADF1 (AtADF1) expression level induce a significant effect on the overall cellular actin-bundling state.…”
Section: Actin Bundling Versus Depolymerization Forcesmentioning
confidence: 99%
“…The only known influences on these rates are proteins of the ADF/cofilin family, which are present at significant concentrations in cells, $20 lM. 1,12,14,44 Cofilins bind preferentially to ADP-bound subunits in actin filaments and accelerate depolymerization of these filaments by increasing the off-rate of ADP-actin subunits, 9 severing filaments to create more ends, 31 and increasing the Pi release rate on ADPAEPi-bound subunits. 5 However, it is not clear what the relative contributions of these three effects are and how they relate to the concentration of cofilin.…”
Section: Parameter Choicesmentioning
confidence: 99%
“…These proteins bind the ADP-bound subunits of filaments found most prominently near pointed ends. 9 Cofilins destablize filament structure leading to both filament severing 31 and enhanced depolymerization. 9 Also regulating the actin cycle in cells are proteins that cap the barbed and pointed ends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation